Templated tibial plateau leveling osteotomy and implant guidance system improves accuracy in novice surgeons: an ex vivo study - Wyatt, Tyler J.; Lynch, Albert C.; Miniter, Brianna (Frontiers in Veterinary Science, 2026)
ObjectiveIntroduce and compare the accuracy of a templated tibial plateau leveling osteotomy and implant guidance system (ProCut TPLO) to the traditional tibial plateau leveling osteotomy (TPLO) in novice surgeons.MethodsTen participants without osteotomy experience completed a TPLO (n = 10) and ProCut TPLO (n = 10) using canine cadaveric limbs. Deviation from intended tibial plateau angle (TPA), distance of eccentricity (DOE), osteotomy trajectory along proximodistal and craniocaudal axes, procedure time, and technical errors were compared. For ProCut TPLO limbs, a trajectory indicating pin was compared to the executed osteotomy trajectory along proximodistal and craniocaudal axes.ResultsProCut TPLO resulted in TPAs that deviated less from target (0.36° vs. 5.6°, p = 0.001), a DOE that was more centered (0.8 mm vs. 7.8 mm, p = 0.001), an osteotomy that was more parallel to joint surface (1.5° vs. 4.4°, p = 0.009) and perpendicular to sagittal plane (2.6° vs. 8.4°, p = 0.002), and took less time (23.1 min vs. 40.9 min, p = 0.005). Mean proximodistal and craniocaudal trajectory deviation from the ProCut TPLO trajectory indicating pin was 0.3° and 0.4°, respectively. No technical errors occurred with ProCut TPLO.ConclusionThe ProCut TPLO yielded more accurate technical execution across all metrics compared to the traditional TPLO and thus may offer novices an accurate and efficient method of executing TPLOs.